Diverging contaminant profiles and prokaryotic assemblages in Arctic and Antarctic lake sediments - Rappazzo, Alessandro Ciro; Lo Giudice, Angelina; Giannarelli, Stefania; Rizzo, Carmen; Tomei, Alessio; Ghezzi, Lisa; Cairns, Warren R. L.; Azzaro, Maurizio; Papale, Maria (Frontiers in Microbiology, 2026)
IntroductionPersistent organic pollutants (POPs) and trace metals are increasingly recognized as critical drivers of ecological change in polar environments. However, their combined impact on sediment microbial communities remains largely unexplored.MethodsWe analyzed sediments from 12 high-latitude lakes and ponds, five from the Arctic (Svalbard) and seven from the Antarctic (South Shetland Islands/Deception Island), to examine contaminant profiles (polychlorinated biphenyls [PCBs] and trace metals) and prokaryotic community structure using 16S rRNA gene amplicon sequencing. Finally, we assessed the associations between the identified communities and detected pollutants, and compared these associations across lakes and sites.ResultsThe results revealed distinct chemical signatures between poles: Arctic sediments were mainly contaminated by polycyclic aromatic hydrocarbons (∑PAHs, 18.5–685.7 ppb; phenanthrene was the most abundant), whereas Antarctic sediments showed relatively higher concentrations of chlorobenzenes (∑CBs, 1.9–3.6 ppb) and polychlorinated biphenyls (∑PCBs, 0.9–1.4 ppb), with 2-methylnaphthalene as the most abundant PAH. Manganese was the most abundant metal in both regions, reaching 760 ppm in the Arctic, while elevated arsenic and lead characterized specific Antarctic sites. Amplicon sequencing identified five dominant phyla (i.e., Actinobacteriota, Bacteroidota, Alpha- and Gammaproteobacteria, and Desulfobacterota) with significant compositional shifts between poles.DiscussionNotably, the distinct contaminant signatures between regions appeared to be associated with shifts in microbial community composition, suggesting that both the type and intensity of POP and metal exposure may influence bacterial diversity and ecological functions in polar lake sediments. These findings provide a robust baseline for Arctic–Antarctic comparisons, positioning polar lakes as sensitive sentinels of contaminant-driven ecological change. They also underscore the urgent need for functional studies and long-term monitoring to evaluate ecosystem resilience under accelerating climate change.